The relationship between thermal sensation and cardiovascular patients' admission rates in Tabriz, Iran. (December 2022) - Roshan, GholamReza; Halabian, Amirhossein; Moghbel, Masoumeh
Abstract: Atmospheric conditions in any place can affect people's health. In recent years, researchers have focused on heat stress and its effect on the exacerbation of some diseases. The main objective of this study is to identify the bioclimatic conditions and its relationship with the admission rate of cardiovascular patients in of Tabriz city. In addition to meteorological variables, daily cardiovascular patient admission rates were obtained from Shahid Madani Heart Hospital in Tabriz during the statistical period of March 27th, 2007 to February 17th, 2017. To do so, the bioclimatic conditions of Tabriz were identified on a daily scale based on bioclimatic indices including Perceived Temperature (PT), Physiological Equivalent Temperature (PET) and Predicted Mean Vote (PMV). Then, the relationship between each bioclimatic condition and the number of cardiovascular patients' referrals in Tabriz was investigated using Kruskal-Wallis test. Findings illustrated that the impact of cold stress in the rate of cardiovascular patients was more than that of the warm stress, which was obtained for all study indicators in a similar way. On the other hand, the results showed that based on PET and PMV indices, there is a significant difference between various bioclimatic classes in the rate of cardiovascular patients' admission. The results of Kruskal-Wallis test include Sig = 0.040 and Sig = 0.049 for PET and PMV, respectively. However, Sig values for and PT indice showed no significant difference between bioclimatic classes in the rate of admission of cardiovascular patients. Generally, it was found that there is a significant difference (Sig = 0.000) between the three classes of bioclimatic cold, warm and comfort with the number of hospital admissions of cardiovascular patients. Highlights: The maximum frequency of admissions of CVD patients in Tabriz was related to periods with cold stress. Only PET and PMV showed a significant difference in admissions of CVD patients due to bioclimatic. Cold stress conditions was more than heat stress in Tabriz according to most of the used indices.